Increased EPO Levels Are Associated With Bone Loss in Mice Lacking PHD2 in EPO‐Producing Cells. (13th May 2016) - Rauner, Martina; Franke, Kristin; Murray, Marta; Singh, Rashim Pal; Hiram‐Bab, Sahar; Platzbecker, Uwe; Gassmann, Max; Socolovsky, Merav; Neumann, Drorit; Gabet, Yankel; Chavakis, Triantafyllos; Hofbauer, Lorenz C; et al.
ABSTRACT: The main oxygen sensor hypoxia inducible factor (HIF) prolyl hydroxylase 2 (PHD2) is a critical regulator of tissue homeostasis during erythropoiesis, hematopoietic stem cell maintenance, and wound healing. Recent studies point toward a role for the PHD2‐erythropoietin (EPO) axis in the modulation of bone remodeling, even though the studies produced conflicting results. Here, we used a number of mouse strains deficient of PHD2 in different cell types to address the role of PHD2 and its downstream targets HIF‐1α and HIF‐2α in bone remodeling. Mice deficient for PHD2 in several cell lineages, including EPO‐producing cells, osteoblasts, and hematopoietic cells (CD68:cre‐PHD2 f/f ) displayed a severe reduction of bone density at the distal femur as well as the vertebral body due to impaired bone formation but not bone resorption. Importantly, using osteoblast‐specific (Osx:cre‐PHD2 f/f ) and osteoclast‐specific PHD2 knock‐out mice (Vav:cre‐ PHD2 f/f ), we show that this effect is independent of the loss of PHD2 in osteoblast and osteoclasts. Using different in vivo and in vitro approaches, we show here that this bone phenotype, including the suppression of bone formation, is directly linked to the stabilization of the α‐subunit of HIF‐2, and possibly to the subsequent moderate induction of serum EPO, which directly influenced the differentiation and mineralization of osteoblast progenitors resulting in lower bone density. Taken together, our data identify the PHD2:HIF‐2α:EPO axis as a so far unknown regulator of osteohematology by controlling bone homeostasis. Further, these data suggest that patients treated with PHD inhibitors or EPO should be monitored with respect to their bone status. © 2016 American Society for Bone and Mineral Research.